From 0d5bcaea3370697822675d9f8d25bca34c02505e Mon Sep 17 00:00:00 2001 From: Chimrod <> Date: Thu, 9 Nov 2023 16:04:09 +0100 Subject: Made the compose evaluation lazy --- lib/syntax/compose.ml | 71 ++++++++++++++++++++++++++++++++------------------- 1 file changed, 45 insertions(+), 26 deletions(-) (limited to 'lib/syntax/compose.ml') diff --git a/lib/syntax/compose.ml b/lib/syntax/compose.ml index dcc1a86..670249a 100644 --- a/lib/syntax/compose.ml +++ b/lib/syntax/compose.ml @@ -14,60 +14,79 @@ module Expression (E : S.Expression) = struct signatures differs a bit from the standard signature as they get the result from E.t in last argument *) - val ident : (S.pos, E.t' * t) S.variable -> E.t' -> t - val integer : S.pos -> string -> E.t' -> t - val literal : S.pos -> (E.t' * t) T.literal list -> E.t' -> t - val function_ : S.pos -> T.function_ -> (E.t' * t) list -> E.t' -> t - val uoperator : S.pos -> T.uoperator -> E.t' * t -> E.t' -> t - val boperator : S.pos -> T.boperator -> E.t' * t -> E.t' * t -> E.t' -> t - - val v : E.t' * t -> t' + val ident : (S.pos, E.t' Lazy.t * t) S.variable -> E.t' Lazy.t -> t + val integer : S.pos -> string -> E.t' Lazy.t -> t + val literal : S.pos -> (E.t' Lazy.t * t) T.literal list -> E.t' Lazy.t -> t + + val function_ : + S.pos -> T.function_ -> (E.t' Lazy.t * t) list -> E.t' Lazy.t -> t + + val uoperator : S.pos -> T.uoperator -> E.t' Lazy.t * t -> E.t' Lazy.t -> t + + val boperator : + S.pos -> + T.boperator -> + E.t' Lazy.t * t -> + E.t' Lazy.t * t -> + E.t' Lazy.t -> + t + + val v : E.t' Lazy.t * t -> t' (** Convert from the internal representation to the external one. *) end module Make (M : SIG) : S.Expression with type t' = M.t' = struct - type t = E.t * M.t + type t = E.t Lazy.t * M.t type t' = M.t' - let v : t -> t' = fun (type_of, v) -> M.v (E.v type_of, v) + let v' : E.t Lazy.t -> E.t' Lazy.t = Lazy.map E.v + let fst' : 'a Lazy.t * _ -> 'a = fun v -> Lazy.force (fst v) + let v : t -> t' = fun (type_of, v) -> M.v (v' type_of, v) let ident : (S.pos, t) S.variable -> t = fun { pos; name : string; index : t option } -> - let t' = E.ident { pos; name; index = Option.map fst index } in - let index' = Option.map (fun (e, m) -> (E.v e, m)) index in - (t', M.ident { pos; name; index = index' } (E.v @@ t')) + let t' = lazy (E.ident { pos; name; index = Option.map fst' index }) in + let index' = Option.map (fun (e, m) -> (v' e, m)) index in + (t', M.ident { pos; name; index = index' } (v' t')) let integer : S.pos -> string -> t = fun pos i -> - let t' = E.integer pos i in - (t', M.integer pos i (E.v t')) + let t' = lazy (E.integer pos i) in + (t', M.integer pos i (v' t')) let literal : S.pos -> t T.literal list -> t = fun pos litts -> - let e_litts = List.map litts ~f:(T.map_litteral ~f:fst) in let litts' = - List.map litts ~f:(T.map_litteral ~f:(fun (e, m) -> (E.v e, m))) + List.map litts ~f:(T.map_litteral ~f:(fun (e, m) -> (v' e, m))) in - let t' = E.literal pos e_litts in - (t', M.literal pos litts' (E.v t')) + let t' = + lazy + (let e_litts = List.map litts ~f:(T.map_litteral ~f:fst') in + E.literal pos e_litts) + in + (t', M.literal pos litts' (v' t')) let function_ : S.pos -> T.function_ -> t list -> t = fun pos f expressions -> let e = List.map ~f:fst expressions - and expressions' = List.map ~f:(fun (e, m) -> (E.v e, m)) expressions in + and expressions' = List.map ~f:(fun (e, m) -> (v' e, m)) expressions in - let t' = E.function_ pos f e in - (t', M.function_ pos f expressions' (E.v t')) + let t' = + lazy + (let e' = List.map ~f:Lazy.force e in + E.function_ pos f e') + in + (t', M.function_ pos f expressions' (v' t')) let uoperator : S.pos -> T.uoperator -> t -> t = fun pos op (t, expr) -> - let t' = E.uoperator pos op t in - (t', M.uoperator pos op (E.v t, expr) (E.v t')) + let t' = lazy (E.uoperator pos op (Lazy.force t)) in + (t', M.uoperator pos op (v' t, expr) (v' t')) let boperator : S.pos -> T.boperator -> t -> t -> t = fun pos op (t1, expr1) (t2, expr2) -> - let t' = E.boperator pos op t1 t2 in - (t', M.boperator pos op (E.v t1, expr1) (E.v t2, expr2) (E.v t')) + let t' = lazy (E.boperator pos op (Lazy.force t1) (Lazy.force t2)) in + (t', M.boperator pos op (v' t1, expr1) (v' t2, expr2) (v' t')) end end -- cgit v1.2.3